2014
DOI: 10.4172/2167-0846.1000137
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Pain And Its Management: Knowledge Of Nurses At Selected Health Institutions, Offering Cancer Treatment In Addis Ababa, Ethiopia, 2013

Abstract: Background: Around a third of patients with cancer report moderate to severe pain and with the development of metastases, the incidence of pain increases to 40% to 60% of patients, and in far advanced disease, 60% to 90% of patients report significant pain. Majority of health professionals found in Ethiopia do not know how to holistically assess and control pain and only insignificant numbers are familiar with the World Health Organization (WHO) pain management protocol. Hence, this study is conducted to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Another finding in this study was that healthcare providers tended to disbelieve patients’ reports of pain. This finding is comparable to those from a previous study, wherein doctors tended to believe that patients overreported their pain more than nurses; as a result, patients complaining of pain were given a placebo ( Nega et al, 2014 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Another finding in this study was that healthcare providers tended to disbelieve patients’ reports of pain. This finding is comparable to those from a previous study, wherein doctors tended to believe that patients overreported their pain more than nurses; as a result, patients complaining of pain were given a placebo ( Nega et al, 2014 ).…”
Section: Discussionsupporting
confidence: 85%
“…A perceived healthcare provider barrier was a lack of knowledge and skills in assessing and managing cancer pain. Various studies found that nurses and doctors did not have adequate knowledge about pain assessment and management ( Nega et al, 2014 ; Omran et al, 2014 ; Toba et al, 2019 ). Javier et al (2016) and Toba et al (2019) determined that inadequate pain assessment by medical staff, which may be due to inadequate knowledge, an underestimation of the patient's complaint of pain, or inadequate communication and listening skills, were significant barriers that prevent the adequate control of cancer-related pain.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge deficiency might be due to serious deficiencies in the undergraduate nursing education curriculum which does not incorporate palliative care as it is needed (7,11). Even if this finding regarding nurses' knowledge is not enough to give care, it is higher than the findings of studies done in Palestine (20%), India (21%), Saudi Arabia (38%), and Addis Ababa (30.5%, 26.5%) (7,8,12,13,14). This might be due to the difference in the study period that the previous studies were conducted before five years when in-service training and formal palliative care education were not adequate.…”
Section: Discussionmentioning
confidence: 63%
“…However, it disagrees with a study done in public hospitals in Addis Ababa. In the previous study, there is no association between the level of education and knowledge of nurses on palliative care (13,14). The possible reason for this discrepancy may be due to the difference in case flow in which the previous study was done in a more urbanized setting than the current study.…”
Section: Discussionmentioning
confidence: 79%